Macaque studies of vaccine and microbicide combinations for preventing HIV-1 sexual transmission - Barouch, Dan H. (National Academy of Sciences, 2012)
Vaccination and the application of a vaginal microbicide have traditionally been considered independent methods to prevent the sexual transmission of HIV-1 to women. Both techniques can be effective in macaque models, and limited efficacy has been observed in clinical trials for each. Here, we have addressed whether vaccines and microbicides can be used together to provide reinforced protection against virus challenge of rhesus macaques. In two separate experiments, four groups of animals were vaccinated with a T-cell–based adenovirus (Ad) vectored vaccine aimed at reducing postinfection viral loads and/or a partially effective dose of a vaginal microbicide aimed at blocking infection of a high-dose vaginal challenge with SIVmac251 or SHIV-162P3. In the first study, the only two protected animals were in the group that received Ad26/Ad5HVR48 vaccine vectors combined with the fusion inhibitor T-1249 as the vaginal microbicide before SIVmac251 challenge. In the second study, vaccination with Ad35/Ad26 vectors combined with the CCR5 inhibitor maraviroc as the vaginal microbicide led to significant reductions of both acquisition of infection and postinfection viral loads following SHIV-SF162P3 challenge. As expected, the vaccine by itself reduced viral loads but had no acquisition effect, whereas the microbicide had a partial acquisition effect but minimal impact on viral loads. For both measures of protective efficacy, the vaccine–microbicide combination differed more from controls than did either separate intervention. Overall, the data suggest that vaccines and microbicides are complementary techniques that may protect better when used together than separately.